PENGARUH KARAKTERISTIK PERUSAHAAN, KOMITE AUDIT DAN KUALITAS AUDITOR TERHADAP COST OF DEBT - Rizka Puji Hastuti; Auliffi Ermian Challen (LPPM Universitas Ibnu Sina, 2023)
This study aims to analyze the characteristics of the company, the audit committee and the quality of the auditor on the cost of debt. The characteristics of the company used are company age, company size, leverage, and profitability. The type of data used in this study is secondary data. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique is a purposive sampling method that produces a sample of 20 companies. The method of data analysis uses multiple regression analysis with SPSS. The results of this study indicate that the age of the company has a positive effect on the cost of debt. The size of the company, the audit committee, and the quality of the auditor negatively affect the cost of debt, while the leverage and profitability do not affect the cost of debt